2020
DOI: 10.21873/cgp.20207
|View full text |Cite
|
Sign up to set email alerts
|

STRA6 Expression Serves as a Prognostic Biomarker of Gastric Cancer

Abstract: Background: Despite advances in our understanding on the pathogenesis of gastric cancer (GC), patients face a poor prognosis. To improve clinical outcomes, effective approaches to diagnosis and treatment employing new diagnostic biomarkers are required to achieve early detection and predict recurrence and prognosis. Materials and Methods: Transcriptome analysis was conducted using surgically resected gastric tissues from four patients with metastatic GC. A total of 228 pairs of primary GC tissues and correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Despite declines in incidence and mortality, GC remains the third leading cause of cancer-related death (1)(2)(3)(4). Unfortunately, patients with GC have a high rate of metastasis specific to the liver and peritoneum, and prognosis is poor in the absence of curative treatment (5)(6)(7). Improved detection and personalized therapies are required to overcome these hurdles.…”
mentioning
confidence: 99%
“…Despite declines in incidence and mortality, GC remains the third leading cause of cancer-related death (1)(2)(3)(4). Unfortunately, patients with GC have a high rate of metastasis specific to the liver and peritoneum, and prognosis is poor in the absence of curative treatment (5)(6)(7). Improved detection and personalized therapies are required to overcome these hurdles.…”
mentioning
confidence: 99%
“…STRA6, a membrane protein, plays a vital role in retinol metabolism and facilitates the transportation of retinol into cells [53]. Recent research has uncovered the involvement of STRA6 in tumor initiation and progression as well as that STRA6 is highly expressed in various tumor cells, such as thyroid cancer [54,55], colorectal cancer [56], lung cancer [57], gastric cancer [20,58], etc., and is associated with prognosis. He et al found that STRA6 can promote the progression of thyroid cancer through the ILK/AKT/mTOR axis [55].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, HPSE, ANO1, and SERPINH1 have been shown to be prognostic indicators of ESCC (38)(39)(40)(41). STRA6, IGFL2, USP2 and CASP14 are associated with the prognosis of other cancers, including hepatocellular carcinoma, bladder cancer, gastric cancer and clear cell renal cell carcinoma (42)(43)(44)(45)(46)(47)(48).The overexpression of CFTR suppressed the proliferation and migration/invasion of ESCC cells and was associated with a good patient prognosis (49). SERPINH1 and BCART1 are associated with various immune checkpoint genes in some cancers (41,50,51).…”
Section: Discussionmentioning
confidence: 99%